(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Over the past century, there have been significant changes in the marketing industry. It is unimaginable how marketing methods, resources, and strategies have changed. Markets in a traditional economy were limited to physical spaces and had various restrictions on time, location, and utility. All markets are now at our fingertips, though, as globalization has shrunk the whole market to the size of a human palm. After starting off as a forum for interpersonal communication, social media has developed into an effective instrument for advertising, brand positioning, and other marketing management tasks. Keeping up with the latest developments in the marketing industry and its tools is crucial for any firm. The purpose of this essay is to draw attention to one of the most important marketing trends.